SOLID DISPERSION TECHNIQUE TO ENHANCE THE SOLUBILITY AND DISSOLUTION OF FEBUXOSTAT AN BCS CLASS II DRUG - Vimalson, D. Christopher; Parimalakrishnan, S.; Jeganathan, N. S.; Anbazhagan, S. (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study was aimed to enhance the solubility of poorly water-soluble drug (BCS Class II) Febuxostat using water-soluble polymers. Methods: Pre-formulation studies like drug excipient compatibility studies by Fourier-transform infrared spectroscopyDifferential scanning calorimetry and determination of saturation solubility of drug individually in various media like distilled water and pH 7.4 phosphate buffer. Solid dispersions of Febuxostat was prepared using Polyethylene glycol (PEG 6000) (fusion method) and Polyvinyl pyrrolidone (PVP K30) (solvent evaporation method) in various ratios like 1:1, 1:2, 1:3 and 1:4 separately. The formulated solid dispersions were evaluated for percentage yield, drug content and in vitro dissolution studies. Results: From the results of pre-formulation studies it was revealed that there was no interaction between drug and excipients and the pure drug was poorly soluble in water. The percentage yield of all formulations was in the range of 54-78 %, and drug content was in the range of 43-78 mg. The solid dispersion containing polyvinylpyrrolidone K 30 in 1:4 ratio showed the highest amount of drug release at the end of 30 min than other formulations. Conclusion: Finally it was concluded that solid dispersion prepared with PVP K-30 in 1:4 ratio by solvent evaporation method was more soluble than by fusion method.